2008
DOI: 10.1007/s11461-008-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of bamboo fiber cellulose in formic acid

Abstract: Bamboo fiber dissolution and hydrolysis in formic acid were studied. After hydrolysis, formic acid can be recovered in a clean state and reused. Solid water-soluble sugars were obtained. After being dipped into the formic acid solution for 30 min, the bamboo fibers started to swell. After one hour, the bamboo fibers gradually started to dissolve in the formic acid solution. The color of the liquor/solution turned green and dark. In the end, the bamboo fibers became thoroughly dissolved in the liquor after four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 30 publications
3
47
0
2
Order By: Relevance
“…The saponifying impact of the mixed alkaline pre-treatment on SCB was verified by a 12% reduction in a band at 1730 cm −1 , which is attributed to saponification of the ester bonds, such as acetyl and uronic ester groups (Peng et al 2012). An increase in absorptions peaks at 1000 −1100 cm −1 in the spectrum of the pre-treated SCB solids demonstrated an increased concentration of cellulose in the pre-treated solid (Sun et al 2008), as already shown by compositional analysis (Table 4).…”
Section: Ft-ir-atr Spectroscopic Analysissupporting
confidence: 76%
“…The saponifying impact of the mixed alkaline pre-treatment on SCB was verified by a 12% reduction in a band at 1730 cm −1 , which is attributed to saponification of the ester bonds, such as acetyl and uronic ester groups (Peng et al 2012). An increase in absorptions peaks at 1000 −1100 cm −1 in the spectrum of the pre-treated SCB solids demonstrated an increased concentration of cellulose in the pre-treated solid (Sun et al 2008), as already shown by compositional analysis (Table 4).…”
Section: Ft-ir-atr Spectroscopic Analysissupporting
confidence: 76%
“…( 1) where C r is the relative crystallinity, whereas F a and F c are the area of noncrystalline and crystal regions, respectively (Sun et al 2008). Each sample was measured at least twice to reduce errors.…”
Section: Methodsmentioning
confidence: 99%
“…Bands at 1000 -1200 cm −1 were related to structural features of cellulose and hemicelluloses. The enhancement of absorption peaks at 1000 -1100 cm −1 after pretreatment indicate the increase in cellulose content in the solid residue [54]. The peak of O-H stretching at 3300 cm −1 and the peak of −CH 2 stretching near 2900 cm −1 are the distinguished features of cellulose.…”
Section: Ftir Spectroscopy Characterization Of Microwave Pretreated Efbmentioning
confidence: 97%